Enhanced Access to Climate-Smart Agriculture and Climate Information Services by Farmers in Mali - Dossou-Yovo, Elliott Ronald; Guindob, Samuel; Sidibec, Mahamoudou; Doumbia, Salif; Diarra, Ba Affoussata; Tchetan, Blaise (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Mali is a rice basket in West Africa, providing a substantial amount of the region's rice supply, but is also highly vulnerable to climate variability and change. AICCRA-Mali aims to strengthen the technical, institutional, and human capacity required to accelerate the wide-scale adoption of climate-smart agriculture and climate information services packages by hundreds of thousands of men and women farmers in Mali. The project focuses on rice and associated speculations (legume, vegetable, tuber, fish, and tree) value chains and pursues to enhance resilience to drought and flooding in rainfed systems and cold and water scarcity in irrigated systems. In 2022, 111,064 farmers including 49% women were supported in the use of CSA and CIS interventions by AfricaRice and the national partners (Syngenta Foundation, Niger office, Mali-Meteo and IER). The focused CSA and CIS interventions were RiceAdvice, drought-tolerant rice varieties, alternate wetting and drying, mechanization services, solar-powered irrigation, GEM parboiling, direct seeding, and information about weather forecasts. The mechanisms used included service provision business models, technologies demonstration followed by farmers' exchange days, save-for-change financing mechanism, Pay-As-You-Go business model, multi-stakeholders’ platforms, and Local Groups for Meteorological Assistance. Application of RiceAdvice recommendations improved rice yield by 0.9 t/ha and farmers’ income by 320 USD/ha. The yield increase was higher in women’s fields (+1.0 t/ha) compared to men’s fields (+0.8 t/ha), which was attributed to the fact that women have culturally access to soils with lower fertility than men’s in Mali, and consequently, the soil responses to applied fertilizers were better in women’s than in men’s fields. When the benefits of the use of RiceAdvice were aggregated over the total area cultivated by the 53,045 farmers, the rice production increase was estimated to be 42966 tones and the farmers’ income increase was estimated to be 15.3 million USD. Farmers who used the solar-powered irrigation pumps increased their income by USD 5,262 per hectare, and improved their food consumption score by 3.1. The food consumption score is the frequency of consumption of different food groups consumed by a household during the 7 days before the survey. The use of solar-powered irrigation technologies enabled farmers to produce cash crops such as onion, tomato, cabbage, and potato during the dry season when fields had previously been abandoned due to water scarcity. Thanks to these additional crops, the increase in their incomes mean they are investing more in quality seeds, and fertilizers.